The Role of the Passive Conditioning in Achieving Thermal Comfort in Temporary Hotel Units: سماح محمد طالب الدويك-سامي أبوطالب-محمد صابر (Al-Academy, 2020)
This research is based on monitoring the local and environmental technologies in the design of the temporary hotel units (nomadic tents) in the desert in the south of Jordan in order to air condition them in summer and winter, maintaining the Jordanian identity, that they are presented with the form and technologies of the age in order to get to the universality. The research adopted the descriptive analytical method and the researcher conducted the analysis of SWOT specified for the analysis of the positive and negative aspects in the design of the temporary hotel units and comparing them with the case studies available in the chosen research area "the Jordanian golden triangle", through the elements of the case under study. The research concluded that the materials today are characterized by their ability to meet the desires of the designers and users at the same time, due to their diversity and the diversity of their properties whether functionally, aesthetically or economically. The research recommended conducting studies and experiments for the properties of the construction materials in terms of pressure, tension and various weather effects when using new construction materials that enable us to get the thermal comfort for the users of the place